2017
DOI: 10.1080/0163853x.2016.1257406
|View full text |Cite
|
Sign up to set email alerts
|

Argument Strength and the Persuasiveness of Stories

Abstract: Stories are a powerful means to change people’s attitudes and beliefs. The aim of the current work was to shed light on the role of argument strength (argument quality) in narrative persuasion. The present study examined the influence of strong versus weak arguments on attitudes in a low or high narrative context. Moreover, baseline attitudes, interindividual differences in working memory capacity, and recipients’ transportation were examined. Stories with strong arguments were more persuasive than stories wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 66 publications
(94 reference statements)
1
23
0
1
Order By: Relevance
“…While traditional approaches to persuasion give importance to the processing of arguments in the attitude change process (e.g., Petty and Cacioppo, 1986 ), models of narrative persuasion devote much less attention to this aspect, for they tend to consider that transportation, or narrative engagement, is the primary vehicle of persuasion when it comes to stories. Our study, like Schreiner et al ( 2018 ), highlights the interest of developing an approach of narrative persuasion that takes into account the arguments that explicitly or implicitly support the beliefs and attitudes that are depicted in the narrative.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…While traditional approaches to persuasion give importance to the processing of arguments in the attitude change process (e.g., Petty and Cacioppo, 1986 ), models of narrative persuasion devote much less attention to this aspect, for they tend to consider that transportation, or narrative engagement, is the primary vehicle of persuasion when it comes to stories. Our study, like Schreiner et al ( 2018 ), highlights the interest of developing an approach of narrative persuasion that takes into account the arguments that explicitly or implicitly support the beliefs and attitudes that are depicted in the narrative.…”
Section: Discussionmentioning
confidence: 58%
“…According to the TIM, the strength of arguments plays a minor role in the narrative persuasion process, for the processing of arguments requires working memory resources that people enjoying a narrative momentarily lack (Green and Brock, 2002 ). However, it has been recently suggested that narratives that included strong arguments about a topic were more persuasive than narratives that included weak arguments, particularly when subjects were initially skeptical about the point advocated in the stories (Schreiner et al, 2018 ). Since CTs are controversial in nature, the last point may be particularly important to understand our results: when a persuasive message is likely to generate skepticism in the narrative recipients, embedding strong arguments in the narrative may be a necessary precondition for persuasion to occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exception is texts-narrations. On the one hand, C. Schreiner, M. Appel, M.-B Isberner, and T. Richter investigated how the inclusion of verbalized (rational) arguments in narrative affect the degree of its persuasiveness, and concluded that argument strength used in narration increases persuasiveness of the entire text [9]. On the other hand, any narrative is structured to make the reader experience emotional evolution.…”
Section: B Persuasive Textsmentioning
confidence: 99%
“…увязывания действий и их результатов (Kendeou et al, 2013), что важно для принятия решений. Эксперименты подтверждают высокую степень убедительности нарративов (Nabi & Green, 2015;Braddock & Dillard, 2016;Schreiner et al, 2018), хотя наибольшая убедительность достигается при сочетании нарративов с количественной, числовой информацией (Zebregs et al, 2015;Hornikx, 2018).…”
Section: роль нарративов в измененияхunclassified